Studies on Feeding and Mangemental Practices Followed By Dog Owners in Gurdaspur and Ropar District of Sub-Mountainous Zone Of Punjab - Singh, Harsimranjeet; Malav, O.P.; Chatli, M.K.; Sethi, A.P.S.; Chahal, Udeybir Singh; Mehta, Nitin; Kashyap , Neeraj (International Journal of Livestock Research, 2019)
Under the present study, dog owners from the Gurdaspur and Ropar districts were surveyed and data regarding the feeding and management of their pets were collected. Dog owners are mainly giving the homemade food. There was significant (P≤0.05) difference in chapatti, rice, meat and egg feeding among the urban and rural dog owners in Gurdaspur district. The quantity of meat given to the dogs in urban area was significantly (P<0.05) higher than the rural areas. 40 dogs from the urban area and 43 dogs from the rural area of Ropar district were selected. There was no significant difference was found among feeding of milk, milk product, curd, sweets, chapatti, dal, rice, vegetable, meat, bone and egg in the diet of dog adopted by the dog owners in urban and rural areas of Ropar district. Average age of pet dogs in District Ropar is higher than Gurdaspur.